Clinical course of five patients definitively diagnosed with idiopathic perilymphatic fistula treated with transcanal endoscopic ear surgery - Kubota, Toshinori; Ito, Tsukasa; Furukawa, Takatoshi; Matsui, Hirooki; Goto, Takanari; Shinkawa, Chikako; Matsuda, Han; Ikezono, Tetsuo; Kakehata, Seiji (Frontiers in Neurology, 2024)
Objectives An idiopathic perilymphatic fistula (PLF) can be difficult to diagnose because patients present with sudden sensorineural hearing loss (SSHL) and/or vestibular symptoms without any preceding events. In such cases, we currently test for cochlin-tomoprotein (CTP) to confirm the diagnosis of idiopathic PLF because CTP is only detected in the perilymph. In this study, we report the clinical course of five patients definitively diagnosed with idiopathic PLF who underwent PLF repair surgery using transcanal endoscopic ear surgery (TEES). Patients and methods Five patients were initially treated with intratympanic dexamethasone for SSHL, at which time a CTP test was also performed (preoperative CTP test). Due to refractory hearing loss and/or fluctuating disequilibrium, PLF repair surgery using TEES was performed to seal the oval and round windows using connective tissue and fibrin glue. These patients were diagnosed with definite idiopathic PLF based on pre- or intra-operative CTP test results (negative, < 0.4 ng/mL; intermediate, 0.4–< 0.8 ng/mL; and positive, > 0.8 ng/mL). We evaluated pre- and intra-operative CTP values, intraoperative surgical findings via a magnified endoscopic view, and pre- and post-operative changes in averaged hearing level and vestibular symptoms. Results Pre- and intra-operative CTP values were positive and intermediate in three patients, positive and negative in one patient, and negative and positive in one patient. None of the patients had intraoperative findings consistent with a fistula between the inner and middle ears or leakage of perilymph. Only two patients showed a slight postoperative recovery in hearing. Four patients complained of disequilibrium preoperatively, of whom two had resolution of disequilibrium postoperatively. Conclusion A positive CTP test confirms PLF in patients without obvious intraoperative findings. The CTP test is considered more sensitive than endoscopic fistula confirmation. We consider that CTP test results are important indicators to decide the surgical indication for idiopathic PLF repair surgery. In our experience with the five cases, two of them showed improvements in both hearing and vestibular symptoms.